Czynniki determinujące wybór oprogramowania do prowadzenia księgowości w biurze rachunkowym - Stężowska, Joanna (My University, 2013)
Głównym celem pracy jest ukazanie zależności pomiędzy doborem odpowiedniego programu księgowego a zakresem świadczonych usług oferowanych przez biura rachunkowe, liczbą pracowników pracujących w danej jednostce księgowej oraz ilością firm obsługiwanych w poszczególnych formach rozliczenia.

Portraying relations between the selection of the appropriate programme of the accountant and the scope provided is a main purpose of the work of services offered by accounting offices, with the number of employees working in the accountant given to the individual and the quantity of companies waited on at individual forms of the settlement.
Determinants choice of providing software for keeping the books in the accounting office
Keywords: księgowość; rachunkowość; optima; bookkeeping; accounting; optima; accounting office; biuro rachunkowe